Exploration of P-Solubilizing and IAA-producing Rhizobacteria from Saline Environments: Their Effects on Vigna radiata Growth-promotion - Utami, Ni Wayan Anggun Diah; Zulkifli, Lalu; Rasmi, Dewa Ayu Citra; Sedijani, Prapti (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Rhizobacteria that are able to dissolve P and produce IAA can be used as component of biofertilizers to help increase plant growth, which can be a more environmentally friendly fertilizer alternative compared to chemical fertilizers. Rhizobacteria originating from sub-optimal environments have the potential to overcome environmental stress such as osmotic stress. To obtain potential isolates that can be used as biofertilizer, exploration of the rhizosphere of the sentigi (Pemphis acidula) has been carried out from the coast of Gili Sulat, Lombok. The method for isolating and selecting IAA producing bacteria was carried out using the colorimetric test method, while for the P solubilization ability, it was carried out by growing rhizobacteria on Pikovskaya media. Isolate PA6 with the highest IAA producing ability (21 ppm) and PL4 with the highest P solubilizing ability (20.9 ppm), were tested for their effect on the growth-promotion of Vigna radiata cultured on Murphy agar media by measuring the parameters of plant height, root length, fresh weight, and plant dry weight. Based on the One Way ANOVA statistical analysis with a p value ≤ 0.05, it showed that the inoculation of IAA-producing and P solvent rhizobacteria was proven to be able to have a significant effect with significantly different results on increasing plant dry weight. In the future, the isolate obtained can be developed into a biofertilizer component that can be applied in saline and dryland agriculture.